Evaluasi Tata Kelola Teknologi Informasi (TI) Berbasis Tesca Pada Universitas Balikpapan - Anwar Fattah (Pusat Penelitian dan Pengabdian Kepada Masyarakat, 2019)
Corporate governance of information technology (it Governance) has been widely implemented by institutions in the various Colleges of the world. Information technology (it Governance) plays an important role in supporting the achievement of the mission, vision, objectives such Colleges in adapting new technology changes, innovation and environmental change in minimizing the risks and address the vulnerabilities Information technology security. To enhance the role of TI against the continuity of the process of college work, then it takes a measurement of it governance (IT Governance). TESCA is a Framework the governance of information technology as a standard framework in information technology on an utilization of an institution/organisisi. And is used to control the it governance.TESCA is in drawing up the instrument and assess the maturity level of the utilization of information technology on campus. The initiative sponsored by the PT. Telkom Tbk and Economic News. This Insturmen as material guidelines and guidance in conducting an evaluation or assessment of the implementation of IT in college. The goal of the research is to Implement IT Governance/corporate governance of information technology on information systems at the University of balikpapan and its information technology infrastructure that supports the information system, to make it more maximize teaching and learning through the system, determine the level of maturity (maturity level) in information systems and information technology infrastructure that supports information systems at the University of Balikpapan and Make a recommendation of the management of it in accordance with the business strategy and objectives of the University of Balikpapan. The results of the research that based on the results Obtained in just my Assesment that the University entrance 49.004 value of Kerosene into the category of Associate Level (SCORE 40.00-use of 59.99). where the existence of the IT management recommendations that can serve as the IT management considerations how should the management of IT to support the performance of information systems